Reinventing ourselves: new and emerging roles of academic librarians in Canadian research-intensive universities - Ada Ducas; Nicole Michaud-Oystryk; Marie Speare (Библиосфера, 2020)
The academic library profession is being redefined by the shifting research and scholarly landscape, the transformation in higher education, and advances in technology.A survey of librarians working in Canada’s research-intensive universities was conducted to explore new and emerging roles. This study focuses on librarians’ activities in: Research Support, Teaching and Learning, Digital Scholarship, User Experience, and Scholarly Communication. It addresses the scope and nature of the new roles, the skills required to provide new services, and the confidence librarians have in their abilities to perform the new roles. It also reports on librarians’ job satisfaction and their perceived impact on the academic enterprise.